Reading Gossip in Early Eighteenth-Century England - Parsons, Nicola. author. aut Link
XI, 211 p.
Keywords: This book analyzes the relation between print cultures and eighteenth-century literary and political practices and, identifying Queen Anne's England as a crucial moment in the public life of gossip, offers readings of key texts that demonstrate how gossip's interpretative strategies shaped readers' participation in the literary and public spheres.